STUDI EKSPLORASI PRAKTIK CORPORATE SOCIAL RESPONSIBILITY SERTA MOTIF YANG TERKANDUNG DIDALAMNYA (KASUS PERUSAHAAN GO PUBLIK DIBURSA EFEK INDONESIA) - Nor Hadi (Universitas Wahid Hasyim, 2010)
This article describes the scope of practice of social responsibility sejauhmanan conducted by the company, what the underlying motive, as well as the availability of coverage the company made the disclosure in the report tahuanan. The research on this topic empirically based argument that echoes of the past decade It was not followed konsiten by the company in implementing social responsibility, as accountability and openness. The came a series of questions, why is there a company inconsistent behavior, there is a motive behind it, what and how can any portrait of the implementation of social responsibility that has been The results showed that the availability of corporate accountability and openness in annula report are at a higher gap, ie there are companies doing with full disclosure kesereiusan, even the number of social disclosures reach 600 items. On the other hand, there are also companies simply do disclosure obligations suggested by the rules, even the number of social pengungakapn less than 30 items. The reason that companies use in tersebuit disclosure is a trade of cost and benefit, which, more economic motives as tendencius. The Company made further disclosures using large part because of social pressure system (system epproech). Viewed from the aspect of social responsibility strategy implementation, there are three approaches, namely: (1) philantrppic, (2) semi-productive partnerships, and (3) productive partnership. Keywords: Social Responsibility, Motive Aprroarch, System Approch, Philantrpic; Community Development. Keywords: Social.